Subcutaneous delivery of FGF21 mRNA therapy reverses obesity, insulin resistance, and hepatic steatosis in diet-induced obese mice - Stefano Bartesaghi; Kristina Wallenius; Daniel Hovdal; Mathias Liljeblad; Simonetta Wallin; Niek Dekker; Louise Barlind; Nigel Davies; Frank Seeliger; Maria Sörhede Winzell; Sima Patel; Matt Theisen; et al. (Elsevier, 2022)
Fibroblast growth factor 21 (FGF21) is a promising therapeutic agent for treatment of type 2 diabetes (T2D) and non-alcoholic steatohepatitis (NASH). We show that therapeutic levels of FGF21 were achieved following subcutaneous (s.c.) administration of mRNA encoding human FGF21 proteins. The efficacy of mRNA was assessed following 2-weeks repeated s.c. dosing in diet-induced obese (DIO), mice which resulted in marked decreases in body weight, plasma insulin levels, and hepatic steatosis. Pharmacokinetic/pharmacodynamic (PK/PD) modelling of several studies in both lean and DIO mice showed that mRNA encoding human proteins provided improved therapeutic coverage over recombinant dosed proteins in vivo. This study is the first example of s.c. mRNA therapy showing pre-clinical efficacy in a disease-relevant model, thus, showing the potential for this modality in the treatment of chronic diseases, including T2D and NASH.